Simulation-Driven Portfolio Scheduling for Scientific Workflows - Soares, João Antonio; Cavalheiro, Gerson Geraldo H. (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2025: Anais da XXV Escola Regional de Alto Desempenho da Região SulDO - 10.5753/eradrs.2025.6801, 2025)
This paper proposes portfolio scheduling approach for scientific workflow management systems (WMS). The goal is to improve scheduling decisions by dynamically selecting suitable scheduling policies during workflow execution. The portfolio integrates multiple task scheduling and resource allocation strategies, considering both computational and network characteristics.